#### Answer

z=-1

#### Work Step by Step

5z+7=6(z-2)-4(2z-3)
5z+7=6(z)-6(2)-4(2z)-4(-3)
5z+7=6z-12-8z+12
5z+7=(6z-8z)+(-12+12)
5z+7=-2z+0
5z=-2z-7
5z+2z=-7
7z=-7
z=$\frac{-7}{7}$
z=-1

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

z=-1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.